Analisis Vegetasi Tumbuhan Herba di Hutan Lingkungan Kampus Unwira Penfui Kupang - Sombo, Imelda Tidora; Sepe, Florentina Y.; Nau, Getrudis W.; Buku, Maria Novita I.; Djalo, Aloysius (BIO-EDU: Jurnal Pendidikan Biologi, 2020)
This study aims to determine the spread of herbal vegetation in the environment of the campus environment of UNWIRA Penfui Kupang, by applying vegetation parameters including density, relative density, frequency, relative frequency, dominance, relative dominance, Importance Value Index (INP), and Comparison Important Value (SDR). The method used in this study is the quadratic method, with the determination of the sampling point divided into two observation stations, based on open and sheltered areas with each station there are 5 observation plots with a size of 1x1 m2. The results of research conducted in the environment of the campus environment of UNWIRA Penfui Kupang found 7 types of herbal plants namely Solanum nigrum, Mussaenda frondosa, Oplismenus hirtellus, Amaranthus viridis, Eclipta L, Bidens pilosa, Imperata cylindrical and the composition of the highest number of individuals were Oplismenus hirtellus. The amount of diversity index value of basket grass plants (Oplismenus hirtellus) is 0.146 with a large amount of basket grass plants tend to be more stable compared to the other 6 plants found. Index value of vegetation diversity of herbaceous plants obtained is 0.782, so species diversity is lacking.